Preoperative C-reactive protein to albumin ratio may be a good prognostic marker in patients undergoing hepatectomy for hepatocellular carcinoma: a meta-analysis - Wang, Shi; Xu, Shengqian; Wang, Jun; Ye, Hailin; Zhang, Kai; Fan, Xiaopeng; Xu, Xiaoya (Frontiers in Nutrition, 2024)
Background: Systemic inflammatory response represented by C-reactive protein to albumin ratio (CAR) was shown to be associated with long-term outcome in patients with hepatocellular carcinoma (HCC). We conducted a meta-analysis to investigate the prognostic value of preoperative CAR in patients undergoing hepatectomy for HCC. Methods: We searched four databases (PubMed, Embase, Scopus and Cochrane Library) from inception to May 10th, 2024. Studies investigating the prognostic value of preoperative CAR in HCC patients after hepatectomy. The primary endpoints were overall survival (OS) and disease-free survival (DFS). Data from individual studies were aggregated to calculate the pooled hazard ratio (HR) using a random-effects model. Results: A total of 11 studies included 4066 patients were finally analyzed in the meta-analysis. Overall, the higher preoperative CAR was associated with poorer OS (HR 1.92, 95% CI 1.67 to 2.22, I2=0%) and DFS (HR 1.79, 95% CI 1.59 to 2.02, I2=0%) rate. Furthermore, subgroup analyses indicated that CAR could be a prognostic biomarker for patients with HCC regardless of regions and cut-off value. Conclusions: Our meta-analysis indicates that higher preoperative CAR level is associated with poorer OS and DFS, it may be a good prognostic marker of survival outcomes after hepatectomy in patients with HCC. However, future prospective trials are necessary to validate the conclusion.